Annual editions archaeology - Parker, Mari Pritchard; Angeloni, Elvio (McGraw-Hill Education Create TM, 2017)
"The Annual Editions series is designed to provide convenient inexpensive access to a wide range of current articles from some of the most respected magazines, newspapers and journals published today. Annual Editions are updated on a regular basis through a continuous monitoring of over 300 periodical sources. The articles selected are authored by prominent scholars, researchers, and commentators writing for a general audience. Each Annual Editions volume has a number of features designed to make them especially valuable for classroom use; including a brief overview for each unit, as well as Learning Outcomes, Critical Thinking questions, and Internet References to accompany each article" -- Amazon.